The growth of ultralong ZnTe micro/nanostructures : the influence of polarity and twin direction on the morphogenesis of nanobelts and nanosheets - Magen, Cesar (2013)
Although ZnTe nanobelts present an intriguing platform to study various optical properties and phenomena in semiconductors, there was very limited study regarding the crystalline structure and defects of ZnTe nanobelts. Here, we correlate the structural properties and features in the crystal of ZnTe nanobelts with the resulting as-synthesized morphology. Ultralong ZnTe nanobelts were synthesized to reach the subcentimeter length scale. Two types of nanobelts were identified according to whether tapering was present and discerned on the basis of crystallinity and polarity of the structure. We conclude that tapered sheetlike nanobelts have Te-terminated lateral facets that induced lateral growth, whereas untapered nanobelts have facets that are nonpolar and nonreactive. Axial and transversal twins were also observed, where the polarity was conserved across twinning boundaries.